Effects of brain breaks on physical activity, academic self-efficacy, emotion regulation, sleep and resilience among Chinese university students - Mengyuan, Zhao (2024)
Encouraging physical activity is vital for university students' well-being. Brain Breaks, an online video program designed for classrooms, has shown positive effects on primary and secondary school students but is rarely used among university students. This study sought to explore the associations among physical activity, academic self-efficacy, emotion regulation, sleep, and resilience in Chinese university students from Jiangsu Province. It also aimed to assess the impact of the Brain Breaks physical activity program on these variables among students at Jiangsu Vocational University of Medicine in Yancheng city. The study consisted of two phases: Phase 1 (a cross-sectional study) and Phase 2 (a cluster-randomised trial). In Phase 1, 1534 participants completed questionnaires, which were translated using forward and backward method. The data were split randomly into two groups: 737 for confirmatory factor analysis (CFA) and 797 for structural equation modelling (SEM). Phase 2 involved 103 Chinese university students in the mixed analysis of variance (ANOVA). Chinese versions of the Brunel Lifestyle Physical Activity Questionnaire (BLPAQ-C), Academic Self-efficacy Scale (ASES-C), Emotion Regulation Questionnaire-8 (ERQ-8-C), Jenkins Sleep Scale (JSS-C), and Five-by-Five Resilience Scale (5×5RS-C) were used to measure physical activity, academic self-efficacy, emotion regulation, sleep and resilience among university students. After the validity and reliability of the questionnaires and the relationship between the variables were determined, Phase 2 was performed to explore the effects of the intervention on the measured variables. Participants, divided by classes, underwent an eight-week intervention, with the experimental group engaging in Brain Breaks physical activity five times a week for five to ten minutes per session. Both groups completed the questionnaire before and after the intervention. The collected data were analysed with SPSS 26.0 for descriptive statistics and mixed ANOVA, Mplus 8.3 for CFA and SEM. In phase 1, most participants were female (70.40%). After removing items with low factor loadings and/or adding correlated residuals within the same factor, all models exhibited good fit. The questionnaires of Chinese version were determined, and the final structural model fitted the data of the questionnaire well. The SEM produced a significant inter-relationship between the variables, with nine specific hypotheses supported by the final model. In Phase 2, the majority of participants also comprised females (71.84%). There was a significant time effect for planned physical activity (p < 0.001) and suppression (p = 0.020). The interaction effect was significant in the ASES-C (p < 0.001), Optimism (p = 0.001) and Social Support (p = 0.009) in the 5×5RS-C. Other variables were not observed to be statistically significant. The scores for ASES-C showed a significant increase in the experimental group after the intervention. In conclusion, the study: 1) confirmed the above questionnaires’ reliability and validity among Chinese university students; 2) revealed a positive link between physical activity and academic self-efficacy, emotion regulation, resilience, and sleep; 3) suggested an eight-week Brain Breaks intervention could significantly boosts students’ academic self-efficacy, positioning it as a promising strategy to use in university students.